New karyologycal data and cytotaxonomic considerations on small mammals from Santa Virginia (Parque Estadual da Serra do Mar, Atlantic Forest, Brazil) - Di-Nizo, Camilla Bruno; Neves, Carolina Lima [UNESP]; Vilela, Julio Fernando; Silva, Maria Jose de J. (Zoological Inst, 2014)
Atlantic Forest, in the eastern coast of Brazil, is a hotspot of biodiversity of mammals, and Parque Estadual da Serra do Mar (PESM) is the largest continuous area of this biome. Here, we characterized the karyotype composition of the small mammals from Santa Virginia, a region in the northern part of PESM. Specimens were collected from July 2008 to September 2009. We identified 17 species (13 rodents and 4 marsupials) from which 7 exhibited species-specific karyotypes, illustrating the importance of karyotype information in cytotaxonomy. We report for first time the karyotype of Monodelphis scalops (Thomas, 1888) and two new records for PESM: Akodon montensis Thomas, 1913 and Brucepattersonius soricinus Hershkovitz, 1998. Cytogenetic polymorphisms were detected for some species trapped in the area. Our results show the importance of Santa Virginia / PESM in addressing studies for the conservation of small mammal wildlife in the Atlantic Forest.
Keywords: Atlantic Forest; conservation; cytotaxonomy; Monodelphis scalops